Plant growth promoters mediated quality and yield attributes of milk thistle (Silybum marianum L.) ecotypes under salinity stress - Noreen Zahra (Nature Portfolio, 2021)
Abstract Silybum marianum (L.) Gaertn (Astraceae) is a well-reputed medicinal plant mostly utilized for silymarin (Sily) content and oil production, however, the information about Sily contents in achene part is still fragmented under different climatic conditions. In this study four milk thistle ecotypes from Faisalabad (FSD), Gujranwala (GUJ), Quetta (QTA), and Kallar kahar (KK) having an altered achene color were analyzed under salt stress. Application of plant growth promoters (PGPs) is one of the solution for ameliorating the effect of salinity and increasing the quantity and quality traits of milk thistle, so ascorbic acid (AsA), thiourea (TU), and moringa leaf extract (MLE) were soil supplied after developing salinity stress (120 mM with irrigation) at germination stage. Predetermined levels were selected for PGPs such as AsA (500 µM), MLE (3%), and TU (250 µM). Results revealed that all yield related attributes were significantly decreased, while secondary metabolites, pericarp epidermis, pericarp parenchyma, and pericarp seed integument increased under salinity stress. Data suggested that PGPs treatment was helpful to alleviate the deleterious effects of salinity stress and enhance the milk thistle quality and quantity parameters. The ecotypic variations with altered achene color patterns represent an advantage for QTA ecotypes for higher Sily extraction under salt stressed conditions.